Vitamin D metabolites in captivity? Should we measure free or total 25(OH)D to assess vitamin D status? - Bikle, Daniel; Bouillon, Roger; Thadhani, Ravi; Schoenmakers, Inez (The Journal of steroid biochemistry and molecular biology, 2017)
•Free 25(OH)D can be measured directly by a two step immunoassay, ultrafiltration or dialysis. All such assays need further validation.•Free 25(OH)D can also be calculated based on measurements of total vitamin D metabolites, DBP, albumin, and the affinities between the metabolite and the binding proteins.•The measurement of DBP needs validation and standardization, and the affinity for the polymorphic DBP needs reassessment.•Some DBP assays are compromised by unequal affinity of the antibody employed for all known DBP isoforms, and the affinity of DBP for the vitamin D metabolites may vary under different physiologic conditions.•Assays to evaluate functional differences in DBP genetic variants may shed light on the role of DBP in regulating free 25(OH)D levels.•Free 25(OH)D (measured or calculated with the best available methodology) is closely correlated with total 25(OH)D concentrations in healthy adults.•Calculated and measured free 25(OH)D (using the best presently available methods) is lower in African Americans than in US Caucasians. Africans living in The Gambia, in contrast to African Americans, have high total and high free 25(OH)D while having the same DBP/GC genotypes, suggesting that differences in free 25(OH)D are not driven by genetic factors.•Free not total 25(OH)D or 1,25(OH)2D regulates vitamin D actions in all cells tested so far.•Whether free 25(OH)D correlates better than total 25(OH)D to serum PTH, bone mass and bone markers or extra-skeletal endpoints is not yet well established.•The relative importance of free versus total 25(OH)D or 1,25(OH)2D under different physiological and pathological conditions requires further studies. There is general consensus that serum 25(OH)D is the best biochemical marker for nutritional vitamin D status. Whether free 25(OH)D would be a better marker than total 25(OH)D is so far unclear. Free 25(OH)D can either be calculated based on the measurement of the serum concentrations of total 25(OH)D, vitamin D-binding protein (DBP), albumin, and the affinity between 25(OH)D and its binding proteins in physiological situations. Free 25(OH)D can also be measured directly by equilibrium dialysis, ultrafitration or immunoassays. During the vitamin D workshop held in Boston in March 2016, a debate was organized about the measurements and clinical value of free 25(OH)D, and this debate is summarized in the present manuscript. Overall there is consensus that most cells apart from the renal tubular cells are exposed to free rather than to total 25(OH)D. Therefore free 25(OH)D may be highly relevant for the local production and action of 1,25(OH)2D. During the debate it became clear that there is a need for standardization of measurements of serum DBP and of direct measurements of free 25(OH)D. There seems to be very limited genetic or racial differences in DBP concentrations or (probably) in the affinity of DBP for its major ligands. Therefore, free 25(OH)D is strongly correlated to total 25(OH)D in most normal populations. Appropriate studies are needed to define the clinical implications of free rather than total 25(OH)D in normal subjects and in disease states. Special attention is needed for such studies in cases of abnormal DBP concentrations or when one could expect changes in its affinity for its ligands.